“Creative placemaking”: a conceptual model fostering social cohesion in community spaces within residential environments - Dash, Shanta Pragyan; Thilagam, N. Lakshmi (Creativity Studies, 2023)
There has been research on the significance of placemaking as a process for user health and well-being and how that affects their way of life in urban planning and development. Creative placemaking, one of the most effective paradigms for making social sustainability, lacks community attributes for social cohesion in planning and design techniques for community spaces, which is the focus of the study. A conceptual model for the inclusion of the concept of creative placemaking in community open spaces to enhance social cohesion in residential environments are proposed in this study. The study employs a qualitative approach to determine the elements and indicators of creative place placemaking considering placemaking as a social process. Community open spaces in a residential neighbourhood were shown to be developing creative placemaking indicators based on theoretical Research VIZ: a) place attachment, b) connection to nature, c) sense of place, d) place memory, e) happy place mapping, and f) image and identity that altogether significantly could contribute towards effective social cohesion in these spaces.